Applied SOA patterns on the Oracle platform : fuse together your pragmatic Oracle experience with abstract SOA patterns with this practical guide /: fuse together your pragmatic Oracle experience with abstract SOA patterns with this practical guide. (2014) - Popov, Sergeĭ
No abstract available